Fabrication and mechanical behavior of bulk nanoporous Cu via chemical de-alloying of Cu–Al alloys - Chen, Fei; Chen, Xi; Zou, Lijie; Yao, Yao; Lin, Yaojun; Shen, Qiang; Lavernia, Enrique J.; Zhang, Lianmeng (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2016)
We report on a study of the influence of microstructure on the mechanical behavior of bulk nanoporous Cu fabricated by chemical de-alloying of Cu50Al50, Cu40Al60, Cu33Al67 and Cu30Al70 (at%) alloys. The precursor Cu–Al alloys were fabricated using arc melting and bulk nanoporous Cu was obtained by subsequent de-alloying of Cu–Al alloys in 20wt% NaOH aqueous solution at a temperature of 65°C. We studied the microstructure of the precursor Cu–Al alloys, as well as that of the as de-alloyed bulk nanoporous Cu, using X-ray diffraction, scanning electron microscopy and energy dispersive spectrometry. Moreover, the compressive strength of bulk nanoporous Cu was measured and the relationship between microstructure and mechanical properties was studied. Our results show that the microstructure of bulk nanoporous Cu is characterized by bi-continuous interpenetrating ligament-channels with a ligament size of 130±20nm (for Cu50Al50), 170±20nm (for Cu40Al60) and 160±10nm (for Cu33Al67). Interestingly the microstructure of de-alloyed Cu30Al70 is bimodal with nanopores (100'snm) and interspersed featureless regions a few microns in size. The compressive strength increased with decreasing volume fraction of porosity; as porosity increased 56.3±2% to 73.9±2%, the compressive strength decreased from 17.18±1MPa to 2.71±0.5MPa.